Mekanisme Pinjaman Tanpa Bunga Kepada UMKM di Dinas Koperasi dan Perindustrian Kota Bandar Lampung Persfektif dalam Hukum Ekonomi Syariah - Ruslan Abdul Ghofur; Eva Dwiana; Heni Noviarita; Muhammad Zaki; Maimun (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Following the global impact of Covid-19 on the economy, including Indonesia's, the Bandar Lampung City government has introduced an interest-free loan program aimed at UMKM to help revive the country's economy. During this crisis, it is crucial for the government to prioritize the UMKM sector as it plays a significant role in GDP and serves as a crucial source of employment, substituting the production of consumer goods or semi-finished goods. The interest-free and collateral loan program, initiated by the Bandar Lampung City Government through the Office of Cooperatives and Micro Enterprises (Diskop UKM), is designed to bolster the growth of Micro, Small, and Medium Enterprises (UMKM) in the region. The goal is to increase access to capital for MSMEs that do not have collateral or a good credit history, as well as create jobs. The program also promotes the Islamic principles of mutual care and justice. The use of APBD funds and loan requirements have been adjusted to the maqasid al-shariah principle. The Bandar Lampung City Government needs to make updates to improve the effectiveness of this program in terms of transparency, accessibility, requirements, procedures, and risk assessment.